New insight into the effect of mass transfer on the synthesis of silver and gold nanoparticles. Issue 44 (4th October 2018) - Besenhard, Maximilian O.; Baber, Razwan; LaGrow, Alec P.; Mazzei, Luca; Thanh, Nguyen T. K.; Gavriilidis, Asterios
Abstract : Silver and gold nanoparticles were prepared using constant reactant concentrations and temperatures, but different process conditions to alter the mass transfer during synthesis. Abstract : The fact that mass transfer affects noble metal nanoparticle (NP) syntheses is well known, not least because the scale-up of batch processes is anything but trivial. Therefore, this work studies the synthesis of silver and gold nanoparticles in batch reactors using constant reactant concentrations, but different process conditions to alter the mass transfer during the synthesis. Silver NPs were synthesized by reduction of silver nitrate via sodium borohydride in the presence of trisodium citrate. Gold NPs were synthesized using the Turkevich method, reducing tetrachloroauric acid via trisodium citrate. Four synthesis conditions for each NP system were used to investigate the mass transfer effects on the size and dispersity of the NPs. These were the i) slow or ii) fast addition of the concentrated reducing agent to the dilute precursor and the iii) slow and iv) fast addition of the concentrated precursor to dilute reducing agent solutions. Slow addition was performed by adding the reagent dropwise at a rate of 0.5 ml min −1 from a tube suspended above the stirred bulk solution, while fast addition was achieved by adding the reagent near the stir bar tip at a rate of 50 ml min −1 from a tube submerged in the stirred bulk solution. Mixing times of 209 ms for slow and 46 ms for fast reagent addition were determined using the Villermaux–Dushman protocol in combination with a mixing model. The silver NP size ranged from 6.7 to 11.5 nm for the four mixing conditions tested, with the smallest NPs being synthesized by fast addition of sodium borohydride to a silver nitrate solution. Stabilization of the initially formed particles was key to producing smaller and less polydisperse silver NPs in the case of slow reagent addition. The gold NP size ranged from 13.1 to 18.0 nm, with the smallest NPs being synthesized by fast addition of the trisodium citrate solution to the tetrachloroauric acid precursor solution. Faster reagent addition reduced polydispersity, due to a sharper separation of nucleation and growth. The results for both systems highlight the importance of mass transfer in determining the size and degree of polydispersity in batch synthesis of NPs and indicate that the effects are system-dependent.